analysis of genomic rearrangements associated with two variable antigen genes of Trypanosoma brucei. - Young, J R (1982)
Some variable surface glycoprotein (VSG) genes of Trypanosoma brucei undergo duplication and transposition when they are expressed. We report here the cloning of cDNAs coding for two VSGs from the ILtar 1 repertoire. Analysis of the genomes of trypanosomes expressing these and other antigens shows that there is no additional copy of the sequences coding for eight VSG in expressing clones of trypanosomes, and reveals rearrangements analogous to those previously described for the gene for another VSG from this antigen repertoire. The data indicate that duplication does not accompany the expression of these VSG genes. Transposition to a specific expression site cannot be excluded, but would have to involve either a much larger segment of DNA, or movement to a region of much greater homology with the previous flanking sequences, than is observed for VSG genes that are duplicated when expressed. It is reasoned that the control of expression by coupled duplication and transposition is not sufficient to account for the selection of a single VSG gene for expression.